The Level of Happiness and Possibly Related Factors among Medical Students of Khon Kaen University in 2015 Academic Year - Wongratanacheewin, Janista; Vimonvanich, Supagorn; Teeratakulpisarn, Napassorn; Srimanta, Nitirath; Pooparadorn, Lunchakorn; Choorus, Benchaporn; Chitkulsampan, Orawan; Paileeklee, Suchada; Srisaenpang, Sompong (Srinagarind Medical Journal, 2015)
Background and Objectives: There was no happiness study of all six-year medical students in Thailand yet. This study aimed to determine level of happiness and possibly related factors of Khon Kaen University medical students (KKUMS) in 2015 academic year. Methods: This descriptive study had study population as 1,122 KKUMS registered in 2015 academic year. Systematic sampling was applied. Calculated sample size was 453 KKUMS. The 2007 Thai Happiness Indicator was used to obtain the levels of happiness. They composed of 3 levels: greater than, equal to and lesser than general population. Self-administered questionnaires were used. Results: Response rate was 94.0% (426/453). The samples were 49.9% male. They studied in year 1st, 2nd, 3rd, 4th, 5th and 6th for 22.1%, 23.1%, 23.3%, 12.7%, 11.3% and 7.5% respectively. The KKUMS had happiness greater than, equal to and lesser than normal population for 40.0%, 45.8% and 14.2% respectively. The proportion of KKUMS who had happiness greater than or equal to general population was 85.8% (95% CI: 82.0%, 88.9%). Factors possibly related to that happiness were satisfaction in health [ORadj= 5.86 (95% CI: 2.79, 12.32)], self-desire to study medicine [ORadj= 3.58 (95% CI: 1.74, 7.35)], having motorcycle or car [ORadj= 4.76 (95% CI: 1.86, 12.21], prior perception of medical student’s life-style [ORadj= 3.05 (95% CI: 1.44, 6.48)] and preference of joining faculty activities [ORadj=2.50 (95% CI: 1.16, 5.40)]. Conclusion: More than four-fifths of KKUMS had happiness greater than or equal to general population. Five factors possibly related to that happiness were discovered